Latinski klasiki v Hieronimovih pismih - Visočnik, Julijana (Keria (Ljubljana), 2002)
Saint Jerome, one of the four Latin Fathers, was a student of Donatus and thus well-versed in Latin literature. He used this knowledge in his own literary work, which was, however, dedicated to Christianity. In his dreams, he was haunted by the reproach that he was not an adherent of Christ (as he should be, being a monk) but of Cicero. Nevertheless, through years of studies the Latin authors had become such an integral part of him that he was no longer able to put them out of his mind completely. His letters, like his other works, are filled with quotations from and illusions to these so-called pagan authors. A study of these reminscences reveals an entire anthology of Latin literature based on Saint Jerome's preferences.
Keywords: antična književnost; cerkveni očetje; Hieronymus; Latinska književnost; pisma; zgodnje krščanstvo